Stethoscopes with hearing aid use: Case studies - Regina Tangerino de Souza Jacob; Ticiana Cristina de Souza Zambonato; Maria Fernanda Capoani Garcia Mondelli (International Archives of Otorhinolaryngology, 2013)
Summary